MENINGKATKAN MINAT DAN PRESTASI BELAJAR SISWA PASCA PEMBATASAN KEGIATAN MASYARAKAT MELALUI TUTORIAL TEMAN SEBAYA BERBASIS KONTEKSTUAL - Achmad Heru Wahyudi (LPPM STKIP PGRI Sidoarjo, 2022)
The purpose of this study was to determine the increase in student activity and increase in student learning mastery after the restrictions on community activities during the pandemic through Contextual-Based Peer Tutorials, in learning. The learning process is carried out in two cycles. The variables studied are student activeness and student achievement. Active variable data is taken by observation, while learning achievement variable data is taken by tests. This research was conducted in Class XII Light Vehicle Engineering at SMK Negeri 2 Pamekasan for the academic year 2021/2022, with a total of 23 students. Cooperative learning with peer tutors is a learning model in which students work in groups with heterogeneous abilities, assisted by students who are aged almost the same age who are asked for help by the teacher to explain to their friends in the learning process, to help students develop thinking skills and problem solving skills, and become independent learners Learning with peer tutoring cooperative methods can improve the average value of students' interest in learning activities is 70.86 in the first cycle, becoming 81.73 in the second cycle. Cooperative learning with contextual-based peer tutors can also improve student learning achievement, from the average score of 68.26 student achievement test results with a completeness level of 69,56% In the first cycle to an average of 80, with a completeness level of 91,30% in cycle II. Thus the level of completeness II can be stated that classically students have completed. Based on the analysis of the data cycle, it can be concluded that the contextual-based peer tutorial cooperative method has a positive impact on increasing student learning activities in the learning process, especially on improving student achievement after the pandemic.